SPARCS: Exploring Sharing Suggestions to Enhance Family Connectedness - Brush, A.J.; Inkpen, Kori; Tee, Kimberly (Conference on Computer supported cooperative work (CSCW 2008), 2008)
Staying in touch with extended family members can be a challenge in part because of the time and effort required, even with the help of current technologies. To explore the value of sharing suggestions in sparking communication and facilitating sharing between extended families, we iteratively built SPARCS, a prototype that encourages frequent sharing of photos and calendar information between extended families. Results from a five-week field study with 7 pairs of families highlight a number of important features for an ideal sharing system to help families stay connected, including asynchronous chat and easily configurable sharing suggestions.